The Business Efficiency of Agroprocessing of Food Crops Commodities and Horticulture in Increasing Product Competitiveness in Central Sulawesi Indonesia - PRATAMA, M. Fardhal; ANTARA, Made; RAUF, Rustam Abdul; EFFENDY, EFFENDY (Journal of Environmental Management and Tourism; Vol 11 No 1 (2020): JEMT Volume XI Issue 1(41) Spring 2020DO - 10.14505//jemt.v11.1(41).04, 2020)
The agroprocessing subsystem is an important part of the agricultural process after farming, because it should increase the sale value of the second derivative product if it is done efficiently. The potential use of efficient factors could increase the competitiveness of agroprocessing subsystems products. This study aims to analyze the business efficiency of agroprocessing of food crops commodities and horticulture in increasing product competitiveness in Central Sulawesi. The respondents used in this study were 12 companies from the agroindustry business of fried onion and banana chips and 6 companies from the tofu agroindustry. The Data Envelopment Analysis (DEA) model was used to measure the efficiency of the business. The results showed that the majority of agroindustry businesses’ operations were relatively inefficient, both in terms of technical and allocative efficiency, and so there was potential to increase efficiency. Potential cost reduction ranged from 20.00-28.10%; this could be done by adopting the best technology, ensuring the use of quality raw materials and using a skilled workforce, to increase product competitiveness.